WAYS TO INCREASE THE SHARE OF TOURISM IN THE COUNTRY'S GDP - Ayubov I. I.; Amirov T. M. (Scholars Digest Publishing, 2023)
This article talks about the development of the infrastructure of the tourism sector in our country based on modern requirements and the increase in the volume of investments and their effectiveness, which ensures the stability of the economy.
Keywords: investment, GDP, tourism, isolation, logistics, innovative, potential, modernization, technical rearmament, technologies.